Analisis Penerimaan Dan Pengeluaran Kas Dengan Sistem Pengendalian Internal - Fadilla Ayu Cahyani; Arnida Wahyuni Lubis (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
A very important asset for business growth is cash. Since it is the most liquid asset, cash is essential. Companies are required to build an internal control system over cash from the time it is received until it is deposited into the bank to protect it from theft and misuse. In an effort to encourage financial improvement initiatives, our business offers quite good and ideal services at the PT Accounting Services Office. Eriadi Fatkhur Rokhman, a private organization. Cash transactions are always involved in carrying out operational activities. Therefore, the business world must implement an internal control mechanism for cash receipts and payments. The purpose of this research is to determine the effectiveness of the Accounting Services Office's internal control system for cash receipts and disbursements. PT. Eriadi Rokhman Fatkhur A qualitative analysis approach was used in the research strategy. In contrast to internal cash disbursement control, the test results show that the cash receipt system is effective. Meanwhile, the internal control system for cash disbursements has not been effective because various internal business control initiatives, such as placing the treasurer or person in charge of finances in the same room with other employees, have not been implemented properly, and there is no insurance, there is cash in hand as well as the treasurer.